2021
DOI: 10.3390/j4030033
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, Textural, and Sensory Quality of Aloe Vera Leaf Gel Powder Fortified Plain Cake

Abstract: Aloe Vera leaves have great potential as an economic supplement with an adequate nutritional profile. The current study aimed to fortify plain (loaf) cakes with Aloe Vera leaf gel (AVG) powder. AVG was freeze-dried to produce Aloe Vera powder (ALP), and four plain (loaf) cakes were prepared with different proportions of ALP (0, 4, 6, and 8%). ALP contained significantly (p < 0.05) more protein (22.23 vs. 12.24), ash (19.83 vs. 0.64), and iron (175 vs. 3.05) than refined wheat flour (RWF). Along with total p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…The collagen materials demonstrate a proteinaceous nature, while aloe vera stands out for its high concentration of carbohydrates. Both characterizations are consistent with findings in the literature, except for the fiber content (AV), which yielded a percentage value of 059 ± 0.03% due to the filtration method proposed in this study, below the reported literature value of 12.31 ± 2.18% (Ramasamy et al 2015;Prestes et al 2013;Kittiphattanabawon et al 2010;Singha et al 2021;Farid et al 2021;Leal 2015).…”
Section: Bromatological Composition Of Collagen and Aloe Verasupporting
confidence: 91%
“…The collagen materials demonstrate a proteinaceous nature, while aloe vera stands out for its high concentration of carbohydrates. Both characterizations are consistent with findings in the literature, except for the fiber content (AV), which yielded a percentage value of 059 ± 0.03% due to the filtration method proposed in this study, below the reported literature value of 12.31 ± 2.18% (Ramasamy et al 2015;Prestes et al 2013;Kittiphattanabawon et al 2010;Singha et al 2021;Farid et al 2021;Leal 2015).…”
Section: Bromatological Composition Of Collagen and Aloe Verasupporting
confidence: 91%